Primitive neuroectodermal tumor of the uterus: a case report. Issue 2 (1st February 2007) - Mittal, S.; Sumana, G.; Gupta, M.; Gupta, B.
Abstract : Peripheral primitive neuroectodermal tumor is a rare group of tumors belonging to the Ewing's family of tumors. The female genital tract is a rare site of origin and to date there are 14 reported cases in the literature. We hereby report the 15 th case of uterine primitive neuroectodermal tumor in a 24-year-old multipara in the reproductive age group. A 24-year-old multipara presented with pain and mass abdomen. Physical examination revealed a pelvic mass enlarged to 20 weeks size gravid uterus, fixed, tender and hard, occupying the whole pelvis. Magnetic resonance imaging showed a large mass posterior to the uterus. She underwent panhysterectomy and debulking of the tumor. Histopathology confirmed the diagnosis. She developed recurrence of the tumor within a month and is now on chemotherapy.